Digital Transformation to Enhance Digital Marketing Strategies for MSME: Case Study PT. XYZ - Farhan; Lusa, Sofian; Kunto D.A , Himawan; Mutia Mayanda , Alia (The Indonesian Journal of Computer Science, 2024)
Since digitalization spread ubiquitously in almost all industries, many traditional businesses have also joined the trend, including PT. XYZ. This company is a startup company that sells queue machines and kiosks. Since 2019, PT. XYZ runs its business through Indonesia’s e-commerce such as Tokopedia and Shopee. However, many competitors appear to collect more customers which made PT. XYZ is difficult to compete with the market industry as a newcomer. In this queue machine and kiosk industry, PT. XYZ already has an official certification from Indonesia’s government and PT. XYZ machines were produced and painted by themselves. But, these main values don’t increase sales because of the lack of brand awareness. Therefore, the company needs a digital transformation to enhance its digital marketing strategy. This study objective uses BMC, PESTEL, and SWOT to analyze the as-is model and to-be model of the company so that the analysis will have a digital transformation strategy to increase brand awareness and sales. The results of this research show that digital marketing is needed to replace current marketing methods and carry out initiatives related to human resources, organizational structure, policy, technology, and community.